The Relationship of Maternal Health Conditions on the Utilization of Maternity Waiting Homes for Maternity Motherhood - Zufrizal; Ida Yustina; Asfriyati (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Maternity Waiting Homes is a regional government program that aims to reduce maternal mortality. But in reality, there are still many people who do not utilize this facility. The purpose of this study is to determine the relationship of maternal health conditions on the utilization of maternity waiting homes for maternity motherhood. This research is an explanatory survey research with cross sectional design. The study was conducted in Langkat Regency, North Sumatra. The results showed that there was a relationship between maternal health conditions and the utilization of the maternity waiting house for maternity motherhood in Langkat Regency (p = 0.027).